Cholesterol pathways affected by small molecules that decrease sterol levels in Niemann-Pick type C mutant cells. - Madalina Rujoi; Nina H Pipalia; Frederick R Maxfield (PLoS ONE, 2010)
Niemann-Pick type C (NPC) disease is a genetically inherited multi-lipid storage disorder with impaired efflux of cholesterol from lysosomal storage organelles.The effect of screen-selected cholesterol lowering compounds on the major sterol pathways was studied in CT60 mutant CHO cells lacking NPC1 protein. Each of the selected chemicals decreases cholesterol in the lysosomal storage organelles of NPC1 mutant cells through one or more of the following mechanisms: increased cholesterol efflux from the cell, decreased uptake of low-density lipoproteins, and/or increased levels of cholesteryl esters. Several chemicals promote efflux of cholesterol to extracellular acceptors in both non-NPC and NPC1 mutant cells. The uptake of low-density lipoprotein-derived cholesterol is inhibited by some of the studied compounds.Results herein provide the information for prioritized further studies in identifying molecular targets of the chemicals. This approach proved successful in the identification of seven chemicals as novel inhibitors of lysosomal acid lipase (Rosenbaum et al, Biochim. Biophys. Acta. 2009, 1791:1155-1165).